2009
DOI: 10.1111/j.1365-2702.2008.02732.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effects of an Internet education programme on newborn care in Taiwan

Abstract: Results suggest that Internet education about newborn care may contribute to greater care knowledge and maternal confidence. Relevance to clinical practice. Internet newborn-care education programmes can achieve success in promoting newborn care and provide health professionals with evidence-based intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 36 publications
(38 reference statements)
1
32
0
Order By: Relevance
“…The fact that maternal confidence is gained during the postpartum process supports previous research (Kobayashi, 2012;Kuo, Chen, Lin, et al, 2009). During the postpartum period in the hospital, a mother learns the basics of caring for her child.…”
Section: Changes In Maternal Confidence 1 Month After Giving Birthsupporting
confidence: 70%
“…The fact that maternal confidence is gained during the postpartum process supports previous research (Kobayashi, 2012;Kuo, Chen, Lin, et al, 2009). During the postpartum period in the hospital, a mother learns the basics of caring for her child.…”
Section: Changes In Maternal Confidence 1 Month After Giving Birthsupporting
confidence: 70%
“…Regarding the adoption of e-learning in nulliparous women, Lin's study on satisfaction of pregnant women in Taiwan (14), Huang and colleagues' study on lactating mothers' awareness in the postpartum period (12) and the study of Kuo et al on women's awareness regarding newborns care in Taiwan, showed that computer-based training is more effective than the control group that received only the routine training (15).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the severe effects of pain on the outcomes of labor (2) and the effect of improving the quality of prenatal education on maternal (15) and newborn health as well as the absence of a study on the impact of education on the knowledge about management of labor pain and by comparing two methods of booklet and e-learning, the present study aimed to compare the effect of instructional software and booklet on mothers' knowledge level about the management of labor pain.…”
Section: Introductionmentioning
confidence: 99%
“…They defined the maternal self-confidence as the mother's understanding of her ability to take care of her children and correct interpretation of the signals (6). Kuo et al reported that maternal self-confidence facilitates the development of the maternal role and promotes the optimal child growth and development (7). Considering the breadth of information required to mothers and some non-scientific beliefs in the face of a newborn (especially in the case of mothers who gave birth of their first child), mothers should be taught key points about everyday care Copyright and manner of dealing with common problems in the neonatal period (1).…”
Section: Introductionmentioning
confidence: 99%
“…Kuo et al (2009), in a study entitled "the impact of e-learning program on the newborns care in Taiwan", showed that e-learning program was more effective in infant care than the routine control method (7). Furthermore, in the study entitled "comparing the effect of e-learning and training booklet on women's' satisfaction of postpartum care", Mohammadi-rizi et al (2012) showed that e-learning can increase satisfaction levels of nulliparous women in the postpartum period (14).…”
Section: Introductionmentioning
confidence: 99%